2020
DOI: 10.1186/s12864-020-07265-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing identified a 16 kilobase deletion on ECA13 associated with distichiasis in Friesian horses

Abstract: Background Distichiasis, an ocular disorder in which aberrant cilia (eyelashes) grow from the opening of the Meibomian glands of the eyelid, has been reported in Friesian horses. These misplaced cilia can cause discomfort, chronic keratitis, and corneal ulceration, potentially impacting vision due to corneal fibrosis, or, if secondary infection occurs, may lead to loss of the eye. Friesian horses represent the vast majority of reported cases of equine distichiasis, and as the breed is known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The aberrant hairs arise from ectopic hair follicles close to the meibomian glands in the eyelid and mostly emerge from the duct openings of the meibomian glands on the margin of the eyelid as single or multiple hairs [ 2 , 3 ]. The disorder is common in dogs but has also been reported in cats [ 4 ], ferrets [ 5 ], and horses [ 6 ]. It is seen in both purebred and mixed-breed dogs [ 1 , 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant hairs arise from ectopic hair follicles close to the meibomian glands in the eyelid and mostly emerge from the duct openings of the meibomian glands on the margin of the eyelid as single or multiple hairs [ 2 , 3 ]. The disorder is common in dogs but has also been reported in cats [ 4 ], ferrets [ 5 ], and horses [ 6 ]. It is seen in both purebred and mixed-breed dogs [ 1 , 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While valuable, annotation of regulatory regions based solely on homology with other species is not expected to be sufficient given the evolutionary role of these elements within and among species (Schmidt et al, 2010 ; McLean et al, 2011 ; Shibata et al, 2012 ; Lowdon et al, 2016 ). With the first publication of the equine FAANG data from eight prioritized tissues (Kingsley et al, 2020 ) and the four “adopted” tissues presented in this manuscript, researchers can begin to interrogate the role of regulatory regions in equine traits, such as the recent investigation of a novel 16 KB deletion associated with an ocular disorder known as distichiasis (Hisey et al, 2020 ). Future annotations for the horse will include maps of regulatory states characteristic of healthy tissue, making it a vital resource to compare against disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Using genome-wide chromatin immunoprecipitation sequencing (ChIP-seq) for these four marks in eight prioritized tissues in the two female FAANG horses, Kingsley et al reported over one million putative regulatory sites [69]. The utility of these data were demonstrated when a 16 kB intergenic deletion associated with an ocular condition in horses, namely distichiasis, was discovered and FAANG ChIP-seq data showed that this region harbors a tissue specific active enhancer [70]. Undoubtedly, these data will continue to aid in the understanding of other structural variants causing or associated with disease in the horse as additional tissues are evaluated.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Just three years after starting the tissue and data collection for the equine FAANG initiative, the community has completed over 400 experiments from more than 50 tissues using a variety of assays targeting different features of the horse regulatory landscape (Table 2). Data are being made available to the public as they are generated and evaluated for passing quality control measures; these data have been and continue to be utilized in unrelated research projects [5,70,115]. Integrated analysis is currently ongoing to provide a systematic annotation of major functional elements in the horse genome available, as a central hub hosted on UCSC genome browser to the research community.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%